Technology application of district heating system with Co-generation based on absorption heat exchange. (October 2015) - Li, Yan; Fu, Lin; Zhang, Shuyan
Abstract: Aiming to explore the energy saving potential of Co-generation and improve the feasibility of district heating, a new type of district heating system with Co-generation based on absorption heat exchange (Co-ah system) has been proposed. It can improve the heating capacity and the energy efficiency by recycling the waste heat from the exhausted steam, and enhance the delivery capacity of the heat network by increasing the temperature difference between the supply and the return water. This paper focuses on the first large-scale industrial application project built in Datong City, China. The delivery capacity of the heat network had increased by 40%, and the heating capacity of the Co-generation system had increased by 50% due to the Co-ah technology. Study of the process design and the operation scheme of the Co-ah system have been introduced in this paper. By experiment methods, the feasibility and reliability of the Co-ah technology have been verified. In addition, through the analyses of measured data in the practical operation condition, the optimum operation condition is determined. Highlights: Introduce the demonstration project of Co-ah technology in north China. The integration design method of the Co-ah system is presented. The performance of the Co-ah system is verified to be distinct. The optimum operation condition is determined in the practical condition.